A comprehensive analysis of urological surgical procedures at DOW University hospital in Karachi Pakistan - A retrospective study - Malik Amna Khatoon; Muhammad Asim; Hammad Mithani; Rashid Bin Hamid; Naranjan Lal; Wareesha Iqbal; Faseeh (Liaquat Medical Research Journal)
The objective of this study was to investigate the indications and the variety of urological surgical procedures conducted at DOW University Hospital in Karachi, Pakistan over a two-year period. This retrospective observational study was conducted from April 2021 to April 2023 including 1773 patients, recruited by using non-probability consecutive sampling technique. Information was obtained from the clinical notes of patients, records of emergency department, and the main electronic database of the hospital. A total of 1773 patients fulfilling the inclusion criteria were included in the present study, with a mean age of 38.73±16.09 years. The majority of the participants were males. The most frequently detected diagnosis in this study was Renal Calculi (28.3%), followed by BPH (11%), and ureteral stones (8%). Among the day-case surgeries, DJ removal was the most common procedure (19%). The most often encountered diagnoses and indications for surgery were renal and ureteral calculi and benign prostatic hyperplasia (BPH). Implementing a dedicated day surgery center and hiring additional specialized healthcare personnel, would improve the caliber and volume of urological services offered at Dow University Hospital.